Development process for integrated water resources management plan under a bottom-up participation perspective - Kuntiyawichai, Kittiwet; Sri-Amporn, Winai; Plermkamon, Vichian (Engineering and Applied Science Research, 2014)
This article presents the development process for the integrated water resources management and development plan of Maha Sarakham Province by considering the priority and urgency of water problem issues. Gathering feedback from stakeholders and prioritizing water management and development projects are also taken into consideration. In view of integrated plans, the project is classified into short-, medium- and long-term plans with the project duration of 2 years, 3 years and 5 years, respectively. In this case, the plans can be categorized into proposed provincial and local plans. Firstly, the comprehensive provincial plans can be divided into 2 groups, i.e. district plans with the total number of 532 plans, which comprise of 505 projects for coping with drought and 27 projects for flood mitigation, and provincial plans from 13 agencies with the amount of 513 projects, which include 396 projects and 117 projects for dealing with drought and flood, respectively. Secondly, there are 4,099 of local plans to be put in place, in which 3,973 projects and 126 projects are proposed to handle drought and flood problems, respectively. From the analysis, it is found that if all planned drought relief projects are implemented, the water demand for domestic and agricultural needs could be covered by 96% and 51%, respectively. In case of the entire proposed flood alleviation projects are executed, 29% of the total flood prone areas can be effectively protected.